Hadith of the Prophet PBUH as a Remedy for Hedonism - Muktashim Billah; Zulfahmi Alwi; Abdul Rahman Sakka (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Because the world is mortal, Islam is a complete religion that is the solution to all problems. Islam regulates the way of human life based on needs and does not splurge, making enjoyment the goal of life. The Prophet warns his people not to be extravagant, greedy, or oblivious to the world. However, the emergence of a lifestyle trend makes enjoyment. Enjoyment of life and endless satisfaction is a disease. Hedonistic behaviorcauses perpetrators to be excessively consumptive without realizing that if their income sources are limited, the impact of hedonistic actors will be wasteful, irresponsible, and in debt to the worst corruption. This paper addressed the Prophet's hadith as a solution to hedonism. Sahih (valid) hadiths are found by using the takhrj hadith method (validation) and examining its content using the taḥlīli (analytic) method by revealing the ontology, epistemology, and axiology sides. From the way of seeking sustenance and always seeking the lawful in order to benefit human life and avoid hedonistic behavior.